Description of the final stadium larva of Telebasis obsoleta (Selys, 1876) (Odonata: Coenagrionidae) - Lozano, Federico; Muzón, Javier; Scattolini, Celeste (Zootaxa, 2012)
The final stadium larvae of Telebasis obsoleta is described and illustrated based on one reared specimen from Argentina.Notes on habitat and new provincial records of Odonata are also provided. The larva of Telebasis obsoleta has five palpalsetae, a feature shared only with the larva of T. demerara. All other known Telebasis species have six or seven palpal setae.Telebasis obsoleta and T. demarara can be distinguished by the presence of two small denticles near the tip of the prementum in T. obsoleta, and by the color pattern of the distal half of the caudal lamellae.